Assessment and management of B3 breast lesions with atypia: a focused review - YOLDEMİR, AHMET TEVFİK; GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT (TAYLOR & FRANCIS LTD, 2020)
Breast lesions with atypia are a spectra of diseases that confer increased risk of breast cancer because of an increased probability of finding concomitant cancer after excision, or evolution toward in situ or invasive cancer over the long term. The widespread use of radiologic tools and core needle breast biopsies, in recent years, has led to an increase in the diagnosis of these atypical breast lesions. Concurrent with this has been an improvement in the classification and pathogenesis of these lesions. Current evidence suggests that the recognition and treatment of patients with atypical histology after biopsy and surgical excision requires a multidisciplinary approach to decrease the overdiagnosis and overtreatment risks. This focused review investigates the controversy and current management of atypical ductal hyperplasia, lobular neoplasia, flat epithelial atypia, and intraductal papilloma with atypia along with the risk-reducing strategies.
Keywords: B3 breast lesions; atypia; uncertain malignant potential; breast cancer; breast surgery; CARCINOMA-IN-SITU; SURGICAL ADJUVANT BREAST; CORE-NEEDLE-BIOPSY; DUCTAL HYPERPLASIA; LOBULAR NEOPLASIA; BOWEL PROJECT; CANCER; RISK; DIAGNOSIS; ULTRASOUND